Is Social Support a Cause or Consequence of Depression? A Longitudinal Study of Adolescents - Ren, Ping; Qin, Xingna; Zhang, Yunyun; Zhang, Ruiping (Frontiers in Psychology, 2018)
A large body of literature has examined the relations between social support and depression. However, the exact nature and direction of these relations are not well understood. This study explored the relations between specific types of social support (peer support and teacher support) and depression. Adolescents (ages 11 to 17) for the first time (N = 2453) participated in a two-wave, six-month longitudinal study. Structural equation modelling was used to test between a social causation model (deficits in social support increase the likelihood of depression), interpersonal theories of depression (depression leads to social erosion), and a reciprocal influence model. Depression influenced peer support significantly and negatively. By contrast, the social causation model was not supported. These results held for males and females. Findings suggested that depression resulted in social support erosion. However, the effect was specific to perceived peer support but not to perceived teacher support.